Domestication‐Admixed Atlantic Salmon ( Salmo salar ) Establish a Productive Population in the Wild - Alison C. Harvey; Øystein Skaala; Francois Besnier; Britt Iren Østebø; Anne Grete Sørvik; Per Tommy Fjeldheim; Laila Unneland; Marine S. O. Brieuc; Fernando Ayllon; Kjell R. Utne; Monica F. Solberg; Kevin A. Glover (Ecology Letters, 2026)
Widespread aquaculture escapes have led to domestication‐admixture in many wild Atlantic salmon populations, widely regarded as a threat to their evolutionary trajectory and persistence amid historically low population numbers. Although decades of research document reduced fitness of domesticated‐admixed offspring in the wild, productivity measurements of domestication‐admixed or feral salmon populations are lacking. Over a 10‐year period, we document colonisation of a river by highly (average 37%) domestication‐admixed salmon using up‐ and downstream traps, genomic data and genetic identification of over 4000 spawners and smolts. Colonisers were identified as strays originating from admixed neighbouring rivers. The resulting population now displays freshwater and marine productivity within ranges observed in wild populations. Our data therefore demonstrate that domestication‐admixed individuals can rapidly establish populations in the wild, likely facilitated in this case by an absence of local competition. Furthermore, high levels of domestication admixture do not preclude a productive population trajectory.

Genomic Landscape of Divergence in Ballan Wrasse ( Labrus bergylta ) - Eeva Jansson; Fernando Ayllon; Carl‐Johan Rubin; Laura Casas; Fran Saborido‐Rey; Tomasz Furmanek; Marine S. O. Brieuc; David Villegas‐Rios; María Quintela; Rolf B. Edvardsen; Roger Lille‐Langøy; Kevin A. Glover (Molecular Ecology, 2025)
The architecture underpinning genomic divergence is still a largely uncharted territory and likely case‐dependent. Here, we investigated genome‐wide variation in Ballan wrasse, a northeastern Atlantic fish species that displays two sympatric colour morphs, spotty and plain, that have been suggested to represent subspecies. We produced a chromosome‐level reference genome and thereafter investigated genomic divergence among 152 individuals including both morphs, from two localities in Spain and Norway each and one in France. Differences between morphs dominated in Spain in accordance with sympatric divergence, whereas in Norway allopatric differentiation was prominent and repeated genomic signals of local divergence were found. Chromosomes had large low‐recombining areas shared across all populations. Within the Spanish morphs, these areas contained large islands of divergence, totalling ~11% of the genome, and showed high morph specificity and strong selection. The same regions showed frequent admixture in the French morphs and no differentiation in Norway. In contrast, divergent regions observed between sampling localities in Norway were shorter and found throughout the genome. High inbreeding and lower diversity were observed in the Norwegian samples, consistent with the proposed recolonisation bottleneck and subsequent drift. Several genomic regions were significantly associated with morphs and contained tens of genes of diverse functions, suggesting that colouration is unlikely to be the sole driver of divergence. Our results do not support the hypothesis of shared larger genomic features underlying intraspecific colour divergence. Instead, we observe gradual accumulation of differences into low‐recombining regions, likely when additional factors like assortative mating and/or lack of gene flow favour their development.

Production of donor-derived Atlantic salmon progeny using allogeneic surrogate broodstock technology - Lene Kleppe; Diego Crespo; Hilal K. Güralp; Jean-Jacques Lareyre; Kai Ove Skaftnesmo; Fernando Ayllon; Thomas W.K. Fraser; Per Gunnar Fjelldal; Tom J. Hansen (Aquaculture, 2025)

Overruled by nature: A plastic response to environmental change disconnects a gene and its trait - François Besnier; Øystein Skaala; Vidar Wennevik; Fernando Ayllon; Kjell Rong Utne; Per Tommy Fjeldheim; Kaja Andersen‐Fjeldheim; Sofie Knutar; Kevin A. Glover (Molecular Ecology, 2024)
In Atlantic salmon, age at maturation is a life history trait governed by a sex‐specific trade‐off between reproductive success and survival. Following environmental changes across large areas of the Northeast Atlantic, many populations currently display smaller size at age and higher age at maturation. However, whether these changes reflect rapid evolution or plasticity is unknown. Approximately 1500 historical and contemporary salmon from the river Etne in Western Norway, genotyped at 50,000 SNPs, revealed three loci associated with age at maturation. These included vgll3 and six6 which collectively explained 36%–50% of the age at maturation variation in the 1983–1984 period. These two loci also displayed sex‐specific epistasis, as the effect of six6 was only detected in males bearing two copies of the late maturation allele for vgll3 . Strikingly, despite allelic frequencies at vgll3 remaining unchanged, the combined influence of these genes was nearly absent in all samples from 2013 to 2016, and genome‐wide heritability strongly declined between the two time‐points. The difference in age at maturation between males and females was upheld in the population despite the loss of effect from the candidate loci, which strongly points towards additional causative mechanisms resolving the sexual conflict. Finally, because admixture with farmed escaped salmon was excluded as the origin of the observed disconnection between gene(s) and maturation age, we conclude that the environmental changes observed in the North Atlantic during the past decades have led to bypassing of the influence of vgll3 and six6 on maturation through growth‐driven plasticity.

Not all lineages are equally invasive: genetic origin and life-history in Atlantic salmon and brown trout acclimated to the Southern Hemisphere - America G. Valiente; Fernando Ayllon; Pablo Nuñez; Francis Juanes; Eva Garcia-Vazquez (Biological Invasions, 2010)

Stock Transfers in Spanish Brown Trout Populations: A Long-term Assessment - Jorge I. Izquierdo; Ana G. F. Castillo; Fernando Ayllon; Jeronimo de la Hoz; Eva Garcia-Vazquez (Environmental Biology of Fishes, 2006)